Risk assessment of infection with severe fever with thrombocytopenia syndrome virus based on a 10-year serosurveillance in Yamaguchi Prefecture - KURODA, Yudai; TAKANO, Ai; SHIMODA, Hiroshi; INOUE, Yusuke; KUWATA, Ryusei; MENDOZA, Milagros VIRHUEZ; TATEMOTO, Kango; ISHIJIMA, Keita; MORIKAWA, Shigeru; TAIRA, Masakatsu (Journal of Veterinary Medical Science, 2022)
In Japan, the first patient with severe fever with thrombocytopenia syndrome was reported in Yamaguchi in 2012. To understand the severe fever with thrombocytopenia syndrome virus (SFTSV) infection in this region, a retrospective surveillance in sika deer and wild boars in Yamaguchi was conducted using a virus-neutralizing (VN) test. The result revealed that 510 of the 789 sika deer and 199 of the 517 wild boars were positive for anti-SFTSV antibodies. Interestingly, seroprevalence in sika deer increased significantly from 2010–2013 to 2015–2020. The SFTSV gene was detected in one of the 229 serum samples collected from sika deer, but not from wild boars. In conclusion, SFTSV had spread among wild animals before 2012 and expanded gradually around 2013–2015 in Yamaguchi.